2017
DOI: 10.1002/jmor.20653
|View full text |Cite
|
Sign up to set email alerts
|

Development of the skull and pectoral girdle in Siberian sturgeon,Acipenser baerii, and Russian sturgeon,Acipenser gueldenstaedtii(Acipenseriformes: Acipenseridae)

Abstract: The head is considered the major novelty of the vertebrates and directly linked to their evolutionary success. Its form and development as well as its function, for example in feeding, is of major interest for evolutionary biologists. In this study, we describe the skeletal development of the cranium and pectoral girdle in Siberian (Acipenser baerii) and Russian sturgeon (A. gueldenstaedtii), two species that are commonly farmed in aquaculture and increasingly important in developmental studies. This study com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 35 publications
(67 citation statements)
references
References 85 publications
(118 reference statements)
3
62
0
Order By: Relevance
“…Parachordals are one of the earliest appearing elements during X. laevis development. This is also the case in Oryzias latipes (Langille & Hall, 1987), sturgeons (Warth et al, 2017) and various anurans (St€ ohr, 1882). Investigations of Rana fusca (now Rana temporaria) indicate similarities in the developmental pattern of anurans (Gaupp, 1906;St€ ohr, 1882).…”
Section: Developmental Sequence Of Cartilage Formationmentioning
confidence: 83%
See 1 more Smart Citation
“…Parachordals are one of the earliest appearing elements during X. laevis development. This is also the case in Oryzias latipes (Langille & Hall, 1987), sturgeons (Warth et al, 2017) and various anurans (St€ ohr, 1882). Investigations of Rana fusca (now Rana temporaria) indicate similarities in the developmental pattern of anurans (Gaupp, 1906;St€ ohr, 1882).…”
Section: Developmental Sequence Of Cartilage Formationmentioning
confidence: 83%
“…The development of the visceral skeleton in X. laevis does not follow the pattern observed in other vertebrates. It has been shown that the viscerocranium of chondrichtyans, sturgeons, and teleosts, as well as anurans, develop in an antero-posterior direction (Gaupp, 1906; Gillis, LUKAS AND OLSSON | 71 Modrell, & Baker, 2012;Langille & Hall, 1987;St€ ohr, 1882;Warth, Hilton, Naumann, Olsson, & Konstantinidis, 2017). In contrast, the ceratohyal is the first cartilage to appear in X. laevis development immediately followed by the palatoquadrate (Figure 3a).…”
Section: Developmental Sequence Of Cartilage Formationmentioning
confidence: 99%
“…The first skeletal elements appear as small aggregations of chondrocytes of the trabecula cranii and the otic capsule (see figure a in Warth et al, ). No obvious chondrocytes are present in the viscerocranium.…”
Section: Resultsmentioning
confidence: 99%
“…Material used for clsm analysis is listed in Table . Additionally, cleared and stained material as listed in Warth et al () was consulted regarding skeletal anatomy and we dissected a specimen of Acipenser gueldenstaedtii (female, 1,280 mm TL) and Acipenser baerii (male, 1,200 mm TL); specimens were not retained.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation